Evaluation of the Mutagenic Potential of Orlistat in Root Merymatic Cells of Allium cepa (Global Journal of Medical Research, 2017)
It has been manufactured constantly, more drugs against obesity, and a great part of these medicines can be bought without prescription, as is the case of Orlistat®. However, some drugs can cause genotoxic effects in the body, which are closely related to carcinogenesis and are therefore capable of cause DNA modifications and can cause great damage to cells. In order to provide information on safety for human health, thus contributing to public health, it is hoped to increase the knowledge about the genotoxic activity of the drug. Orlistat® to provide a broader picture of the possible side effects of this drug. For this, the Allium cepa test with different concentrations of Orlistat® was performed. It was found that the drug induced chromosomal aberrations in meristematic cells of onion root. Genotoxic assessment of medicinal products increases the complexity of assessing its side effects.
Keywords: obesity; genotoxicity; weight loss